2022
DOI: 10.3390/pathogens11101129
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira spp. Prevalence in Cats from Southern Italy with Evaluation of Risk Factors for Exposure and Clinical Findings in Infected Cats

Abstract: Leptospirosis is a worldwide zoonotic disease, but feline leptospirosis is rarely reported. This study aimed at investigating Leptospira spp. prevalence in cats from southern Italy, evaluating risk factors, clinical findings and laboratory data associated with infection. The serum of 112 cats was investigated by microscopic agglutination test (MAT), detecting anti-Leptospira antibodies against 14 pathogenic serovars. Blood and urine samples were tested by a real-time polymerase chain reaction targeting the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…In our study, the serovars that had the highest number of positive samples were serovars Bratislava and Hardjo, and the highest titer seen in cats was against serovar Hardjo (1:3200). Positivity to serovar Bratislava agrees with other feline studies both inside and outside of the United States [26][27][28][29], while a limited number of studies reported positive samples against serovar Hardjo [25,27].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the serovars that had the highest number of positive samples were serovars Bratislava and Hardjo, and the highest titer seen in cats was against serovar Hardjo (1:3200). Positivity to serovar Bratislava agrees with other feline studies both inside and outside of the United States [26][27][28][29], while a limited number of studies reported positive samples against serovar Hardjo [25,27].…”
Section: Discussionsupporting
confidence: 87%
“…Genotyping revealed that two of the positive cat samples were Leptospira interrogans serogroup Icterohaemorrhagiae serovar Icterohaemorragiae or Copenhageni. A similar study by Donato et al, 2022 [ 52 ] detected antibodies against serovars Poi, Bratislava, Arborea, Ballum, Pomona, and Lora in 15.3% (17/111) of cats (titers range: 20–320) and Leptospira spp. DNA in 3% (4/109) of blood and 9% (10/111) of urine samples.…”
Section: Discussionmentioning
confidence: 54%
“…In Leptospira spp. antibody-positive cats, alterations in CBC (anaemia, neutrophilia, monocytosis and eosinopenia), in inflammation markers (i.e., hypoalbuminemia and hyperglobulinemia) and increased ALT activity have been reported [ 51 ]. Previous case reports described three confirmed, naturally infected clinical cases of feline leptospirosis, in which the major clinical findings were different stages of renal insufficiency without any liver involvement [ 24 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors, such as outdoor habits, the presence of livestock and farm animals that may shed Leptospira in the neighbourhood, wild animals’ Leptospira reservoirs, and seasonality, may result in different degrees of exposure to pathogenic Leptospira , thus, potentially justifying the broad ranges of antibody prevalence reported in the literature. A recent study conducted in cats in southern Italy reported antibodies against serovars Poi, Arborea and Mini, among others [ 51 ]. This study also described the spring season as the only risk factor for urinary Leptospira shedding, detected in 9% of urine samples.…”
Section: Discussionmentioning
confidence: 99%